2018
DOI: 10.1080/23273798.2018.1503309
|View full text |Cite
|
Sign up to set email alerts
|

Harry Potter and the Chamber of What?: the impact of what individuals know on word processing during reading

Abstract: During reading, effects of contextual support indexed by N400-a brain potential sensitive to semantic activation/retrieval-amplitude are presumably mediated by comprehenders' world knowledge. Moreover, variability in knowledge may influence the contents, timing, and mechanisms of what is brought to mind during real-time sentence processing. Since it is infeasible to assess the entirety of each individual's knowledge, we investigated a limited domain-the narrative world of Harry Potter (HP). We recorded event-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 66 publications
6
20
0
1
Order By: Relevance
“…It is good to point out that this can also be used to elicit more personally identifying information about an individual. A strong illustration of this is a recent study in which congruency effects were elicited using Harry Potter related stimuli, and the authors found a correlation between the N400 strength to these stimuli and the self-reported familiarity with the Harry Potter fandom [97]. Such an approach could be extended to predict an individual's familiarity with the books, raising ethical considerations: an application based on active mental context, can be subverted more easily than an application that probes your passive (world-) knowledge.…”
Section: Discussionmentioning
confidence: 92%
“…It is good to point out that this can also be used to elicit more personally identifying information about an individual. A strong illustration of this is a recent study in which congruency effects were elicited using Harry Potter related stimuli, and the authors found a correlation between the N400 strength to these stimuli and the self-reported familiarity with the Harry Potter fandom [97]. Such an approach could be extended to predict an individual's familiarity with the books, raising ethical considerations: an application based on active mental context, can be subverted more easily than an application that probes your passive (world-) knowledge.…”
Section: Discussionmentioning
confidence: 92%
“…This effect can be seen in sentence recall (Marks and Miller 1964: [Melting snows cause sudden floods > Melting parties augur fragrant drivers]), verification (Walker 1975: The height of a home ceiling is [9 > 100] feet), target word naming (Stanovich and West 1979: the clothes hung inside the [closet > bridge]), eye fixations during reading (Morris 1994: [the barber trimmed the mustache > the person trimmed the mustache]), and in the N400, a brain response that reflects semantic processing (Kutas and Hillyard 1980: He took a sip from the [waterfall > transmitter]). Findings from the N400 show that comprehenders draw on event typicality (Matsuki, Chow, Hare, Elman, Scheepers and McRae 2011: Donna used [the shampoo to wash her filthy hair > the hose to wash her filthy hair]), culturally-specific knowledge (Hagoort et al 2004: The Dutch trains are [yellow > white > sour], presented in Dutch to Dutch speakers), and even knowledge of fictional worlds (Troyer and Kutas 2018: There are two Beaters on every Quidditch team. Their job is to protect their team from [Bludgers > Spellotape]).…”
Section: Real-world Plausibility In Comprehensionmentioning
confidence: 99%
“…Troyer and Kutas (2018) examined the role of an individual's domain-specific knowledge in eliciting N400 effects by having participants read sentences from the domain of the Harry Potter (HP) novels. Endings that were more or less contextually supported within the HP universe showed N400 effects that were graded according to individual participants' HP knowledge.…”
Section: The N400 As a Long-latency Mmnmentioning
confidence: 99%